TANTANGAN PENDIDIKAN MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Taseman, Taseman (Journal Of Islamic Elementary School (JIES), 2018)
The era of industrial revolution 4.0 or the term Indonesian roadmap making 4.0. will change the structure of human life both ways of life, how to interact and communicate and how to receive information for each person with the emergence of supercomputers (smart phones), internet of things, human-machine interfaces, artificial intelligence or artificial intelligence, autonomous vehicles, 3D printing or digitalization, optimizing the human brain with genetic editing and the development of neurotechnology that combines automation with cyber technology, this needs to be balanced with increasing human resources from the pattern in educating students with learning methods taught in basic education to tertiary education, this will bring changes to design, strategy , methods, approaches and models for delivering material or content in our existing education curriculum. This change brings a shift in the substance of the learning method that has an impact on the change significantly in the learning process which now uses information technology such as the use of laptops, andoid-based smartphones, IOS, internet, and new methods for educators to transform learning more effectively and efficiently, with the methods and strategies used to be able to change the learning outcome resulting from our education, which is expected to face the era of the industrial revolution.